PERAN KELOMPOK SADAR WISATA (POKDARWIS) DALAM PENGEMBANGAN PARIWISATA NAGARI TUO PARIANGAN DI KABUPATEN TANAH DATAR - Arif Wardana; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
In this research using descriptive qualitative research method, there is a purpose to know how the role of Tourism Awareness Group (POKDARWIS) in tourism development of Nagari Tuo Pariangan in Tanah Datar regency. Besides this research also try to know what factors that support Tourism Awareness Group (POKDARWIS) Nagari Tuo Pariangan to develop tourism and do its duty as a driver of regional tourism along with know what factors inhibiting Tourism Awareness Group (POKDARWIS) in doing development tourism to carry out its function as a community representative who plunged directly into the field. Based on the results of research that has been done there are results that show Group Awareness Tours (POKDARWIS) Nagari Tuo Pariangan still has shortcomings and constraints faced in carrying out activities based on the scope of its activities. Knowledge and insight about tourism is known to be inadequate for some of its members, other than that the group members also still do not have the capital and ability or experience enough to be able to manage the business related to tourism and organizational management, in addition to the factors that support the Conscious Travel Group (POKDARWIS) Nagari Tuo Pariangan to develop tourism.Keywords: Pokdarwis, Scope of activities Pokdarwis, Development Tourism.